Implementasi Routing pada OpenFlow Software-Defined Network dengan Algoritme Depth-First Search dan Breadth-First Search - Aprilia Kartika Sriastunti; Rakhmadhany Primananda; Widhy Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Routing is the process of determining the path to convey data from source to destination. In conventional network routing configuration is still not flexible and efficient, because they have to configure network devices manually. Software-Defined Network as a new paradigm in network architecture, has the flexibility and efficiency for centralized network configuration. In SDN, the data plane and control plane are connected by the OpenFlow protocol. Routing on the network can be interrupted because of link disruptions such as link failures that result in the system having to find another pathway to keep communicating. In this research, network routing uses DFS and BFS algorithms, because both has simple concept and better complexity than other routing algorithms such as Dijkstra. The testing parameters are path finding, response time, packet loss, and packet traffic. When at link failure, system can still find another path to continue sending data from the source node to the destination node. The results of response time without link failure, both algorithms have been able to search for the best path based on determining the maximum value of the path on the controller. The average value of packet loss when 1 link down on DFS has the same result as BFS when 2 links down, which is 3.62%. In traffic testing, both algorithms have the same average value of the results of packet transmission to another switch, which is 52.67%.